Factors enhancing word-of-mouth influence: positive and negative service-related messages. Issue 1 (4th February 2014) - Sweeney, Jill; Soutar, Geoff; Mazzarol, Tim
Abstract : Purpose: – This study aims to examine the effects interpersonal, service product and message factors has on positive and negative word of mouth's (WOM) influence. The study also sought to address the impact WOM had on changes in people's willingness to use a service provider. Design/methodology/approach: – A total of 495 consumers who had received positive WOM and 505 who had received negative WOM in the prior 12 months completed an online survey. The sample was recruited through a national online consumer panel provider. Findings: – Positive WOM was more effective and positive WOM messages had a greater effect on people's willingness to use a service than did negative WOM. Paradoxically, the strength of WOM and interpersonal factors had more impact on the influence of negative WOM, while brand equity enhanced positive WOM and acted as a buffer to negative WOM. Research limitations/implications: – The study was conducted in a services context and may not necessarily be generalizable to product contexts. Further, the factors enhancing WOM in online contexts need to be examined, although the present model's constructs (e.g. homophily) are not equivalent in this context. Practical implications: – Different circumstances may enhance or detract from the influence of positive and negative WOM. Managers should maximise the verbal strength of positive WOM messages and generate positive brand equity perceptions, as this offers a buffer to negative WOM. Recommendations also include addressing customer education and socialisation to enhance WOM message influence. Originality/value: – The study extended prior WOM research by addressing interpersonal, service product and message factors, as well as the change in intended behaviour for positive and negative WOM.